Free surface reconstruction of opaque liquids in microgravity, Part 1: Design and on-ground testing. (December 2021) - Romero-Calvo, Á.; García-Salcedo, A.J.; Garrone, F.; Rivoalen, I.; Cano-Gómez, G.; Castro-Hernández, E.; Maggi, F.
Abstract: This paper describes an inexpensive, non-invasive and highly adaptable surface reconstruction device for opaque liquids. The instrument was developed to study the lateral sloshing of ferrofluids in microgravity as part of the UNOOSA DropTES 2019 StELIUM project. Its design is driven by the geometrical and mechanical constraints imposed by ZARM's drop tower, where the experiment was launched in November 2019. The launch catapult and deceleration systems impose strong axial g-loads to a system that is confined in the reduced capsule environment. Redundant procedures are implemented to measure the first two lateral sloshing frequencies and damping ratios of the magnetic liquid, as well as its equilibrium surface in microgravity. Ideal vertical resolutions between 0.25 and 0.4 mm/px can be achieved with the configuration here proposed. The final performance depends, among other factors, on the correct application of the robust calibration procedure that is documented in this work. Highlights: A simple, inexpensive and adaptable liquid surface reconstruction device is presented. Laser projections are employed to compute the free surface elevation profile. The device was developed to study the sloshing of ferrofluids in microgravity. The meniscus shape and oscillation frequencies are easily measured.